2010
DOI: 10.1007/s11274-010-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of an extracellular α-amylase gene from an Antarctic deep sea psychrotolerant Pseudomonas stutzeri strain 7193

Abstract: Psychrotolerant Pseudomonas stutzeri strain 7193 capable of producing an extracellular a-amylase was isolated from deep sea sediments of Prydz Bay, Antarctic. The 59678-Da protein (AmyP) was encoded by 1665-bp gene (amyP). The deduced amino acid sequence was identified with four regions, which are conserved in amylolytic enzymes and form a catalytic domain, and was predicted to be maltotetraose forming extracellular amylase by using the I-TASSER online server. Purification of AmyP amylases from both the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The enzyme used soluble starch, amylose, glycogen, and maltose as substrates and retained 90% of its activity at low temperature with all the substrates. Wang and others (), Ballschmiter and others (), and Zhang and Zeng () reported on amylases from many different extreme environments. In an effort to understand the mechanism of action of GH 57 amylase family, in relation to structure, Blesak and Janecek () studied 2 partially characterized GH 57 nonspecified amylases from an uncultured bacterium by bioinformatics analysis.…”
Section: α‐Amylase Familymentioning
confidence: 98%
“…The enzyme used soluble starch, amylose, glycogen, and maltose as substrates and retained 90% of its activity at low temperature with all the substrates. Wang and others (), Ballschmiter and others (), and Zhang and Zeng () reported on amylases from many different extreme environments. In an effort to understand the mechanism of action of GH 57 amylase family, in relation to structure, Blesak and Janecek () studied 2 partially characterized GH 57 nonspecified amylases from an uncultured bacterium by bioinformatics analysis.…”
Section: α‐Amylase Familymentioning
confidence: 98%
“…LSK25 obtained from Signy Station, South Orkney Islands, maritime Antarctic reported for the production of recombinant lipase that is tolerant to organic solvents ( Salwoom et al, 2019 ). Zhang and Zeng (2011) reported the identification of the amylase gene from the psychrotolerant P. stutzeri strain 7,193. Numerous other Pseudomonas species isolated from the regions like Indian Himalaya ( Salwan et al, 2010 ; Jain and Pandey, 2016 ; Pandey et al, 2019 ; Jain et al, 2020 ), Ny-Alesund, Svalbard, Arctic ( Srinivas et al, 2009 ), Humboldt Glacier, Mount Humboldt, Andean region of Venezuela ( Ball et al, 2014 ) have been studied for production of industrially important enzymes such as amylases, proteases, RNA polymerase and lipases ( Uma et al, 1999 ; Zhang and Zeng, 2011 ; Jain et al, 2017 ; Salwoom et al, 2019 ; Guo et al, 2021 ).…”
Section: Industrial Applicationsmentioning
confidence: 99%
“… Zhang and Zeng (2011) reported the identification of the amylase gene from the psychrotolerant P. stutzeri strain 7,193. Numerous other Pseudomonas species isolated from the regions like Indian Himalaya ( Salwan et al, 2010 ; Jain and Pandey, 2016 ; Pandey et al, 2019 ; Jain et al, 2020 ), Ny-Alesund, Svalbard, Arctic ( Srinivas et al, 2009 ), Humboldt Glacier, Mount Humboldt, Andean region of Venezuela ( Ball et al, 2014 ) have been studied for production of industrially important enzymes such as amylases, proteases, RNA polymerase and lipases ( Uma et al, 1999 ; Zhang and Zeng, 2011 ; Jain et al, 2017 ; Salwoom et al, 2019 ; Guo et al, 2021 ). Beside mountains, the oceans represent an untapped potential that exists in the microbiome to produce enzymes with distinctive properties.…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…In previous investigations, amylases were found in many different extreme environments7912. Nevertheless, no study reported the screening of metagenomic DNA derived from Acid Mine Drainages (AMDs) for any polymer degradation activity.…”
mentioning
confidence: 99%